Design and Implementation of an IoT-Based Misting Control System for Orchid Plants in the ITERA Botanical Gardens - Miranto, Afit; Fil’aini, Raizummi; Ramadhani, Uri Arta; Pertiwi, Kisna; Yulita, Winda; Setiawan, Andika; Mufidah, Zunanik; Astuti, Resti Dwi (Jurnal Multidisiplin Madani, 2023)
Orchids are one type of plant that can be cultivated in a greenhouse. The growth of orchid plants is influenced by several factors, including altitude, light intensity, envirnmental temperature, environmental humidity, and water content in the planting medium. If some of these factors do not meet the needs, then the growth of the orchid plant will be disrupted, the roots and flowers produced by the orchid will not be healthy and beautiful. The aim of this research is to create a system that is able to monitor and control the environmental conditions in the place/location where this orchid grows so that it is always in a stable condition. The technology used is misting misting based on an Android application using sensors and IoT to maintain and maintain the condition of orchid plants so that they are always in optimal condition. In the results of the tests carried out, the data obtained were good, namely that this instrument had an accuracy of 80%. The application that has been created is capable of controlling and monitoring the environmental conditions of orchids very well